If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + 54 = 46 Reorder the terms: 54 + -8x = 46 Solving 54 + -8x = 46 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-54' to each side of the equation. 54 + -54 + -8x = 46 + -54 Combine like terms: 54 + -54 = 0 0 + -8x = 46 + -54 -8x = 46 + -54 Combine like terms: 46 + -54 = -8 -8x = -8 Divide each side by '-8'. x = 1 Simplifying x = 1
| -16x-30=-46 | | 17-43/5 | | -5x-3=7 | | 3y+x+y-x=90 | | 104=1.8x+32 | | -4x-2(2x-9)=58 | | -6x-14=22 | | 5x+2(-6x+13)=-9 | | -5x-3(5x-8)=164 | | .45x+1.25y=200 | | -14x+6=-36 | | 2x-2(-2x-10)=74 | | -4=12X-5 | | 4(y-1)=66 | | 3x+7(-2x-10)=29 | | n+5=72/2 | | 3x+7(2x-10)=29 | | 6x-4(-3x-18)=-108 | | X^4+x^2+1/x^2+1 | | 7x+2(-7x-3)=-83 | | 2x+2(-2x+8)=-8 | | 11[107+(-1y)]-13y=89 | | 6x-7(5x-13)=-112 | | 9.9x+8-3.9x=2 | | x/6=18/9 | | x+y=107 | | -3y+4/5+8/7=-5y/3 | | -3y+4/5+8/7 | | 1-y/6=-6-y/3 | | 8(1.61)+4y=34 | | 11y/6+1/4=y/6-2y/3 | | q+4.5=3q-2.7 |